Intermodel and method comparison of mean radiant temperature from numerical weather prediction models: Evaluation of enhanced spatial resolution in Europe - Oleh SKRYNYK; Pavol NEJEDLÍK; Krzysztof BŁAŻEJCZYK (Contributions to Geophysics and Geodesy)
Thermal stress indices play a vital role in evaluating human health risks related to heat and cold. Mean Radiant Temperature (MRT), derivable from numerical weather prediction (NWP) models, is a critical input for many such indices. This research generates high-resolution (5.5 km × 5.5 km) MRT estimates across Europe using the CERRA NWP system. We evaluate different computational approaches, benchmark the high-resolution MRT against the established ERA5-HEAT dataset, and validate results using BSRN ground observations. The study focuses on diverse European environments. Our high-resolution MRT product demonstrates comparable performance to ERA5-HEAT over flat terrain but offers substantial accuracy gains over complex terrain, including mountainous and coastal regions. These findings highlight the value of enhanced spatial resolution for accurate MRT estimation, crucial for robust thermal stress assessment and contributing to improved environmental health and safety strategies.